Effect of exercise training in patients with cardiac sarcoidosis after induction of oral corticosteroid therapy - Yanagi, Hidetoshi; Konishi, Harumi; Shimada, Yukihiro; Miura , Hiroyuki; Aoki, Tatsuo; Noguchi, Teruo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: To our knowledge, no study has investigated altered muscle strength in patients with cardiac sarcoidosis (CS). This retrospective observational study investigated the relationship between quadriceps isometric strength (QIS) and exercise training (ET) in patients with CS.Methods: Eighteen patients who participated in a 4-month ET programme immediately after initiating oral corticosteroids were studied. They underwent 3–5 ET sessions per week during hospitalisation and 1–2 sessions per week after discharge. We measured their QIS at the beginning of the ET programme and at 1 and 4 months after programme enrolment. The patients received 29±4 mg/day prednisolone during the corticosteroid induction period and 15±4 mg/day prednisolone during the corticosteroid tapering period.Results: They continued ET and showed significant QIS weakness in the early corticosteroid induction period (0.52±0.12 to 0.48±0.11 kgf/kg, P=.048) and no significant improvement during the corticosteroid tapering period (0.53±0.08 to 0.58±0.06 kgf/kg, P=.099). Patients who received ≤12.5 mg/day prednisolone reported an improved QIS-to-body weight ratio.Conclusions:Patients with CS treated with 30 mg/day prednisolone showed poor QIS early in the corticosteroid induction period, even with ET. Patients with CS who receive corticosteroids may be more susceptible to developing corticosteroid myopathy.